Relationship between Perceived Stress with Resilience among Undergraduate Nursing Students - Farzaneh Pourafzal; Naiemeh Seyedfatemi; Mehrnoosh Inanloo; Hamid Haghani (Tehran University of Medical Sciences, 2013)
Background & Aim: The effect of perceived stress on students' health depends on their coping abilities. Resilience is a coping strategy for dealing with the stress. The aim of this study was to determine the relationship between the perceived stress with resilience in undergraduate nursing students .   Methods & Materials: In this cross-sectional study, 309 undergraduate nursing students of Tehran University of Medical Sciences were selected during the first semester of 2012-2013 using the stratified sampling method. Data were collected using the Perceived stress scale and the Connor-Davidson Resilience Scale (CD-RISC). The data were analyzed using descriptive and inferential statistics in the SPSS-14 .   Results: Findings revealed that most of the students (99.3%) had a moderate or high perceived stress. There was a statistically significant relationship between the perceived stress with the resilience (P £ 0.001, r=-0.38) .   Conclusion: The school of nursing should provide facilities and opportunities for students in their 4-year educational program to learn stress management strategies including increasing resilience ability.